Why some things should not be for sale the moral limits of markets - Satz, Debra (New York ; Oxford : Oxford University Press, 2010)
Here, philosopher Debra Satz takes a penetrating look at those commodity exchanges that strike most of us as problematic. What considerations, she asks, ought to guide the debates about such markets?
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Free enterprise -- Moral and ethical aspects; Capitalism -- Moral and ethical aspects